2008
DOI: 10.1038/sj.emboj.7601968
|View full text |Cite
|
Sign up to set email alerts
|

Signaling from β1- and β2-adrenergic receptors is defined by differential interactions with PDE4

Abstract: β1- and β2-adrenergic receptors (βARs) are highly homologous, yet they play clearly distinct roles in cardiac physiology and pathology. Myocyte contraction, for instance, is readily stimulated by β1AR but not β2AR signaling, and chronic stimulation of the two receptors has opposing effects on myocyte apoptosis and cell survival. Differences in the assembly of macromolecular signaling complexes may explain the distinct biological outcomes. Here, we demonstrate that β1AR forms a signaling complex with a cAMP-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(197 citation statements)
references
References 23 publications
10
182
0
5
Order By: Relevance
“…Changes in the molecular composition of signalosomes are associated with receptor desensitization, sequestration of the receptor to subcellular membranous compartments and internalization, all of which strongly influence bAR function [5][6][7][8][9][10][11]. Signaling has also been shown to depend on differential interactions with scaffolding proteins in signaling complexes [12]. Recently we have used near field scanning optical microscopy (NSOM) to demonstrate that functional receptors are organized into multi-protein domains of $140 nm average diameter on murine neonatal and embryonic cardiac myocytes [13].…”
mentioning
confidence: 99%
“…Changes in the molecular composition of signalosomes are associated with receptor desensitization, sequestration of the receptor to subcellular membranous compartments and internalization, all of which strongly influence bAR function [5][6][7][8][9][10][11]. Signaling has also been shown to depend on differential interactions with scaffolding proteins in signaling complexes [12]. Recently we have used near field scanning optical microscopy (NSOM) to demonstrate that functional receptors are organized into multi-protein domains of $140 nm average diameter on murine neonatal and embryonic cardiac myocytes [13].…”
mentioning
confidence: 99%
“…signaling in ventricular cardiac myocytes (Richter et al, 2008), they might facilitate beta-adrenergic signaling after the surge of catecholamines during labor.…”
Section: Discussionmentioning
confidence: 99%
“…PDE4D Is Associated with I Ks Channels in the HeartRecent studies have reported that members of the PDE4D subfamily physically interact, in a direct way or via an adaptor protein, with cardiac target proteins such as ␤-arrestin (33, 34), ␤-adrenergic receptors (33,35), and ryanodine receptors (14,36,37). We next investigated whether PDE4D species are endogenously expressed in mouse heart and whether they interact with I Ks channels.…”
Section: Resultsmentioning
confidence: 99%